Atlas of Normal Imaging Variations of the Brain, Skull, and Craniocervical Vasculature - McKinney, Alexander M. (Springer International Publishing : Imprint: Springer, 2017)
This atlas presents normal imaging variations of the brain, skull, and craniocervical vasculature. Magnetic resonance (MR) imaging and computed tomography (CT) have advanced dramatically in the past 10 years, particularly in regard to new techniques and 3D imaging. One of the major problems experienced by radiologists and clinicians is the interpretation of normal variants as compared with the abnormalities that the variants mimic. Through an extensive collection of images, this book offers a spectrum of appearances for each variant with accompanying 3D imaging for confirmation; explores common artifacts on MR and CT that simulate disease; discusses each variant in terms of the relevant anatomy; and presents comparison cases for the purpose of distinguishing normal findings from abnormalities. It includes both common variants as well as newly identified variants that are visualized by recently developed techniques such as diffusion-weighted imaging and multidetector/multislice CT. The book also highlights normal imaging variants in pediatric cases. Atlas of Normal Imaging Variations of the Brain, Skull, and Craniocervical Vasculature is a valuable resource for neuroradiologists, neurologists, neurosurgeons, and radiologists in interpreting the most common and identifiable variants and using the best methods to classify them expediently. .